Meningkatkan Pendapatan Melalui Daur Ulang Limbah Masyarakat - Pratami, Nur Indah; Zailani, Zailani (Rifa'Institute, 2021)
The problem of garbage is a classic problem that repeatedly faced by the surrounding residents, especially in the Village of Peace. Because of the amount and level of danger, waste, especially plastic waste composed of chemicals, is difficult to decompose so that it is dangerous for the environment, so it is necessary to process waste to turn plastic waste into something useful. Based on surveys in the peaceful village area, North Binjai people still mostly do not have a fixed income. The implementation of the results of plastic bottle waste treatment into liquid hand soap packaging products in Damai Village was carried out to raise awareness of residents and provide ideas on how to increase their income. In addition, it can minimize pollution, so that the residents of The Peace Village can be more concerned about environmental cleanliness. The methods used in the program of utilizing plastic waste as packaging products are divided into two, namely the stage of exposure or explanation and the stage of practice to the community. Through training and mentoring the manufacture of hand washing soap and the utilization of plastic bottle waste, residents get insight into business opportunities that can be created through these creative ideas, and residents are already able to make liquid hand soap that can be sold. Through the training program on making hand soap in Damai Village, it is hoped that it can be an alternative to the use of plastic bottle waste which can be a product that can help improve the economy of the surrounding community.